Antifungal effects of echinocandins diminish when exposed to intestinal lumen contents: a finding with potentially significant clinical implications - Mehravar, Sepideh; Leite, Gabriela S.; Pimentel, Mark; Rezaie, Ali (Frontiers in Pharmacology, 2024)
Echinocandins, a prominent class of antifungals, are known for their broad-spectrum activity and favorable safety profiles. However, their bioavailability and efficacy via oral route are suboptimal. In this study, caspofungin and micafungin, the two most commonly used echinocandins, were evaluated in various in vitro environments simulating intestinal lumen. The results revealed that while both antifungals are effective in standard medium, their efficacy significantly diminishes in the presence of human small bowel aspirates and bovine bile. The study suggests that bowel contents and specifically bile acids may be a suppressive component, hindering the antifungal effects of echinocandins. This novel exploration sheds light on the poor oral bioavailability of echinocandins. The findings imply that echinocandins alone, regardless of administration route, may not be optimal for gastrointestinal (GI) fungal infections or invasive fungal infections originating from intestinal translocation. Further clinical investigations are warranted to validate and expand upon these observations.